PERUBAHAN SOSIAL BUDAYA DAN EKONOMI INDONESIA DAN PENGARUHNYA TERHADAP PENDIDIKAN - Ridwan Idris (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2011)
Education keeps on changing. This change is an implication of the change of all aspects of life in the society. Like wise, education in Indonesia must change along the changes of life in the so-ciety. This study describes social-cultural and economic change which took place due to political instability. It also analyses the impact of such change to education.